Resilience and methodological resistance: Ethnographies of Mozambique during pandemic times: Introduction - Adalima, J.; Carvalho, X.; Florêncio, F.; Jossias, E.; Meneses, M. P. (Anthropology Southern Africa, 2023)
Drawing on Mozambique as a site of ethnographic inquiry, this special issue of Anthropology Southern Africa looks at the intersection of pandemic times and the challenges to the ethnographic method that this poses. The issue presents new ways of rethinking and reimagining the ethnographic method to understand the resilience and methodological resistance that anthropologists working on Mozambique have produced. This introduction (i) explores the pandemic experience, (ii) considers Mozambique as a site of ethnographic inquiry and (iii) concludes with a broader debate on the nature of the ethnographic method in contemporary anthropology.